First Aid Skills of Pre-Service Physical Education Teachers at Batangas State University - Davidsol Mendoza; Mauricio Atienza Junior; Kyla Marie Torino Maralit; Chino Randel Odello (CV Rezki Media, 2023)
Background: The researchers believe acquiring knowledge and first aid skills can improve the instruction of Physical Education. Thus, no matter how proactive a teacher can be, there will be possibilities that an unnecessary situation may occur because it is movement education. Objectives: The study aimed to determine the first aid skills of pre-service physical education teachers at Batangas State University. Specifically, the study determined the respondents' extent of manifestation of competencies in providing first aid skill components as assessed by the instructors and students, along with cardiopulmonary resuscitation, management of bleeding, and fracture. The study also compares the responses of the two groups of respondents. The issues and challenges in developing first aid skills were also ascertained to propose training activities to intensify students' skills and competencies. Methods: This study used descriptive research and a researcher-made questionnaire to gather data from 186 participants, including 159 physical education students and 27 teachers from Batangas State University during the 2021-2022 academic year. Results: The study found that students had moderate competency in applying CPR, recognizing victim situations, and performing two rescue breaths correctly. Similarly, students had moderate competency in managing bleeding and identifying fracture types. However, the two groups of respondents had no significant difference in competency. The biggest challenge identified by students was the need for more training and workshops related to first aid, while linguistic barriers and inconsistent training were less significant challenges. Conclusion: The findings show that Bachelor of Physical Education students greatly manifest first aid skills in CPR, managing bleeding, and treating fractures but need improvements in specific competencies. There was no significant difference in the assessment between the two groups of respondents. However, attendance to training and workshops was the primary issue and challenge in developing the first aid skills of BPEd students.